Cultural Intelligence and Attitudes Towards Multicultural Education: Mediating Role of Intercultural Sensitivity - Munevver Basman , Dilan Bayram (Educational Process: International Journal, 2024)
Background/purpose. The study investigated the role of intercultural sensitivity as a mediator variable between cultural intelligence and attitudes towards multicultural education.